2020
DOI: 10.1371/journal.pone.0238379
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and transcriptomic studies of BGC823 cells stimulated with Helicobacter pylori isolates from gastric MALT lymphoma

Abstract: Background The correlation between the infection of H. pylori and the occurrence of gastric MALT lymphoma (GML) has been well documented. However, the mechanism of how GML is caused by this bacterium is not well understood, although some immunologic mechanisms are thought to be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A total of 32 H. pylori strains (2 isolated from GML patients, 10 each isolated from gastritis patients, gastric ulcer patients and gastric cancer patients) from the H. pylori strain library of the China CDC were used in this study. We performed both transcriptomic and proteomic analyses on gastric cancer cells infected by the two H. pylori isolates from GML patients and the reference strain 26695 in our previous studies, and found specific differentially expressed genes and differentially expressed proteins induced by the GML isolates ( Zou et al., 2020 ). The H. pylori strains were identified by microscopic examination and urease, catalase, and oxidase activity tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 32 H. pylori strains (2 isolated from GML patients, 10 each isolated from gastritis patients, gastric ulcer patients and gastric cancer patients) from the H. pylori strain library of the China CDC were used in this study. We performed both transcriptomic and proteomic analyses on gastric cancer cells infected by the two H. pylori isolates from GML patients and the reference strain 26695 in our previous studies, and found specific differentially expressed genes and differentially expressed proteins induced by the GML isolates ( Zou et al., 2020 ). The H. pylori strains were identified by microscopic examination and urease, catalase, and oxidase activity tests.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used a human gastric carcinoma undifferentiated cell line BCG823 which have been used in previous studies to reveal the proteome variation infected by MALT isolates and other isolates ( Zou et al., 2020 ). The cell line was cultured in RPMI 1640 supplemented with 10% FBS at 37°C in an atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Various biomedical in vivo systems have demonstrated the existence of Hp biofilms in gastric biopsies. Recent transcriptomic and proteomic analyses have provided valuable insights into the transition from planktonic Hp to the biofilm phase, including higher gene expression of adhesins, flagella, toxins, efflux pumps, lipopolysaccharides (LPS), the type IV secretion system, urease, and hydrogenase, for obtaining alternative energy sources [ 56 ]. Conversely, factors involved in quorum sensing, metabolism, and translation are reduced in biofilms [ 57 ].…”
Section: Biofilm-associated Helicobacter Pylori An...mentioning
confidence: 99%
“…By deregulating these pathways, H. pylori might influence gastric lymphomagenesis through modulating the proliferation of cells, inducing autophagy and fostering inflammatory responses and epithelial mesenchymal transition. By proteomic analysis, they also identified 116 differentially expressed proteins, most of them previously associated with cancer that can be used as biomarkers for lymphoma diagnosis or as potential therapeutic targets [ 209 ].…”
Section: Transcriptomicsmentioning
confidence: 99%